The influence of contextual constraint and word length on eye movement control during Chinese reading - Jin, Weiqiong; Liu, Yang; Wang, Suiping (Frontiers in Psychology, 2025)
Given that Chinese text lacks explicit spaces to mark word boundaries, readers need to segment the continuous text into words of varying lengths. Contextual information helps determine word boundaries in Chinese reading. However, it remains unclear how contextual constraint and word length information guide eye movements during Chinese reading. To address this issue, the present study examined the relationship between contextual constraint and word length information in determining when and where to move the eyes in Chinese reading. We manipulated contextual constraint such that the target words were either predictable or unpredictable, and manipulated word length such that the target words were either single-character or three-character. The results demonstrated that both contextual constraint and word length influenced word skipping, fixation durations, saccade lengths, and landing positions. However, we did not find significant interactions between them across all measures. Moreover, Bayes factor analysis provided strong evidence for the absence of an interaction, suggesting that contextual constraint does not modulate the effect of word length on eye-movement control in Chinese reading. These findings advance our understanding of eye-movement control mechanisms in Chinese reading and provide empirical evidence for improving existing models of Chinese reading.